2018
DOI: 10.1177/0379572118774229
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Food Fortification and Biofortification in Low- and Middle-Income Countries: A Review of Programs, Trends, Challenges, and Evidence Gaps

Abstract: In the last 17 years, large-scale food fortification initiatives have been reaching increasingly larger segments of populations in LMIC. Large-scale food fortification and biofortification should be part of other nutrition-specific and nutrition-sensitive efforts to prevent and control micronutrient deficiencies. There are remaining technical and food system challenges, especially in relation to improving coverage and quality of delivery and measuring progress of national programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(148 citation statements)
references
References 66 publications
3
129
0
Order By: Relevance
“…Despite the documented successes of food fortification globally, an unfinished agenda persists, that limits its potential for impact at a global scale. Previous reviews on the state of LSFF [6,8,78,79] have focused on efficacy and effectiveness, coverage and equity, and costs and cost effectiveness. In this review, we (1) identified, based on pre-determined criteria, 84 LMICs that stand to benefit from fortification programs suggesting a need for action; (2) quantified bottlenecks (gaps) to achieving potential to benefit and link these with design and implementation issues; and (3) suggest new areas for innovations across the fortification ecosystem, including some that already hold great promise and others that warrant further research.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the documented successes of food fortification globally, an unfinished agenda persists, that limits its potential for impact at a global scale. Previous reviews on the state of LSFF [6,8,78,79] have focused on efficacy and effectiveness, coverage and equity, and costs and cost effectiveness. In this review, we (1) identified, based on pre-determined criteria, 84 LMICs that stand to benefit from fortification programs suggesting a need for action; (2) quantified bottlenecks (gaps) to achieving potential to benefit and link these with design and implementation issues; and (3) suggest new areas for innovations across the fortification ecosystem, including some that already hold great promise and others that warrant further research.…”
Section: Discussionmentioning
confidence: 99%
“…The process of implementation of micronutrient food fortification programs is challenging, as there are several steps involved in the process of monitoring and evaluation. A review of available documents about lessons learned from various micronutrient food fortification programs identified the following challenges and barriers: [64][65][66][67][68][69][70] (1) Lack of qualified personnel and lack of training; (2) Lack of clear guidelines at the country level on implementation, regulatory frameworks, and monitoring and evaluation; (3) Lack of clarity in the structure and roles of government authorities in regulatory monitoring; (4) Lack of enforcement of standards by the regulatory agents or political instability, which may be related to perceived political risk in doing so; • Mandatory fortification of staple foods (salt with iodine, wheat flour and maize meal with iron, zinc, vitamin A, folic acid, and other B-complex vitamins, sugar and oil with vitamin A and skimmed milk powder with vitamins A and D) • Supplementation programs (mega doses of vitamin A to children and iron and folic acid to pregnant women) and biofortification (sweet potato with β-carotene) Philippines…”
Section: Challenges and Barriersmentioning
confidence: 99%
“…In this sense, several agencies worldwide are focusing their attention on the fight against micronutrient deficiencies, since they are a short-term resolution (FAO, 2017;Prentice et al, 2008). Some challenges, such as choosing appropriate fortification vehicles, having a good policy, targeting populations, avoiding excessive consumption in non-target groups, and monitoring nutritional status, are among relevant factors in improving health and will have the possibility to save billions of lives (Dwyer et al, 2015;Osendarp et al, 2018;Prentice et al, 2008;WHO & FAO, 2006).…”
Section: Issues and Challenges Of Nutrient Deficienciesmentioning
confidence: 99%